Building An Islamic Feminist Liberation Theology For Women In Prostitution - Rahmadi Agus Setiawan (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2019)
Nowadays prostitution tends to be regarded as a moral problem. This claim, in fact, oppresses women in prostitution. Women in prostitution then are regarded as sinners, dirty, and damned. This stigmatization in fact cannot solve the real problem of prostitution, and has made it difficult for women in prostitution to return to society. Based on historical, social and cultural research on prostitution, it can be found that prostitution is a structural problem. Structurally, women in prostitution are victims of poverty, discrimination against women, and domination by patriarchal culture. Stigmatizing women in prostitution nowadays cannot be separated from religion as source of morality. The false interpretation of religion often happens because theology is constructed from a dogmatic-textual orientation. Based on this theology, women in prostitution, of course, are blamed and claimed to be sinners. This perception makes women in prostitution who are oppressed become more oppressed. Based on this problem, then, theology needs to be reconstructed. By considering social and cultural analysis, theology need not become in the future so alienated from actual problems. To support the literary data, field research will be conducted, that is in Pasarkembang, a centre of prostitution in Jogjakarta. To collect data from this field, I will use convenience samples for interviews of women in prostitution. The interview questionnaire is included in the appendix. The interview questions will be based on existing research with the intention of connecting the local situation to theory in liberation theology. Interview questions will be quoted in text to illustrate structural aspects of prostitution. This field study proposes to learn about the presence of structural aspects of prostitution in Islamic society in Indonesia. In investigating Islamic theology, some points can be addressed. The main point is that the situation of many women in prostitution nowadays is analogous with slavery in Muhammad’s day. If we look at al-Qur’an wholly, we will understand that Islam actually wanted to eradicate slavery gradually. Some verses even explicitly forbid people to enslave women. The last step of liberation theology is praxis. In considering the steps within praxis, the insights of Islamic theology, can do best praxis for liberating women in prostitution. But, women in prostitution have also to be included in this praxis. The role of women in prostitution as subjects is very important if they are to liberate themselves.